Two genetically separable steps in the differentiation of thymic epithelium - Nehls, Michael; Kyewski, Bruno; Messerle, Martin; Waldschütz, Ralph; Kutsche, Kerstin; Smith, Andrew J. H.; Boehm, Thomas (Science, 1996)
The development of the thymus depends initially on epithelial-mesenchymal and subsequently on reciprocal lympho-stromal interactions. The genetic steps governing development and differentiation of the thymic microenvironment are unknown. With the use of a targeted disruption of the whn gene, which recapitulates the phenotype of the athymic nude mouse, the WHN transcription factor was shown to be the product of the nude locus. Formation of the thymic epithelial primordium before the entry of lymphocyte progenitors did not require the activity of WHN. However, subsequent differentiation of primitive precursor cells into subcapsular, cortical, and medullary epithelial cells of the postnatal thymus did depend on activity of the whn gene. These results define the first genetically separable steps during thymic epithelial differentiation.